2018
DOI: 10.1007/978-3-319-95165-2_27
|View full text |Cite
|
Sign up to set email alerts
|

Accounting Information System (AIS) Alignment and Non-financial Performance in Small Firm: A Contingency Perspective

Abstract: Accounting Information System (AIS) is very important for Small and Medium Enterprises (SMEs) because it can provide information for the owner in decision making. In line with the result of previous study, which find that AIS alignment is needed because it will affect company performance. This study aims to test the direct relationship and mediating relationship among three contingency variables of AIS alignment on non-financial performance. This study employs questionnaire with 87 SMEs owner in Yogyakarta reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 27 publications
(59 reference statements)
0
22
0
Order By: Relevance
“…Components of AIS (Ganyam and Ivungu, 2019) As shown in the above figure, the components of AIS are based on many components, in which each component is important in reaching the required outputs and with specifications capable of achieving the required (Prasad and Green, 2015). Budiarto et al (2018) indicates that individuals played an important role during the Corona pandemic in achieving the required accounting information systems, as they are the vital component of the system and they are the ones who control the system's functions and inputs by paying attention to the primary data entry mechanism, its validity and accuracy, and Avoid messing with it. As for Haleem et al (2019), it was confirmed that individuals contribute significantly to the quality of the information that the systems produce through internal control, technology and infrastructure requirements, in addition to the daily use of accounting information systems.…”
Section: Components Of Aismentioning
confidence: 99%
“…Components of AIS (Ganyam and Ivungu, 2019) As shown in the above figure, the components of AIS are based on many components, in which each component is important in reaching the required outputs and with specifications capable of achieving the required (Prasad and Green, 2015). Budiarto et al (2018) indicates that individuals played an important role during the Corona pandemic in achieving the required accounting information systems, as they are the vital component of the system and they are the ones who control the system's functions and inputs by paying attention to the primary data entry mechanism, its validity and accuracy, and Avoid messing with it. As for Haleem et al (2019), it was confirmed that individuals contribute significantly to the quality of the information that the systems produce through internal control, technology and infrastructure requirements, in addition to the daily use of accounting information systems.…”
Section: Components Of Aismentioning
confidence: 99%
“…Also, conventional management accounting information has become under strong criticism by scholars and practitioners (Cooper & Kaplan, 1988;Drury, 2007) as being internally rather externally focused, expost oriented (related to past events) rather than ex-ante (related to future events), financially oriented, and according to Wilson (1995), this emphasizes short-term goals. Budiarto et al (2018) investigated the direct link as well as the mediating link among three variables of accounting information system alignment on the firm performance.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…And found that there was statistically significant relationship between accounting systems and the performance. (Budiarto, 2014), investigated the effect of AIS alignments on non-financial performance in SMEs and found that AIS alignment has a significant effect on non-financial performance. (Ironkwe & Otti, 2016), showed that relevance of accounting information was statistically significant in determining the profitability and quality of service delivery of banks in Nigeria.…”
Section: Em-2020-1794mentioning
confidence: 99%